Gate‐Defined Quantum Confinement in CVD 2D WS2. Issue 25 (26th August 2021) - Lau, Chit Siong; Chee, Jing Yee; Cao, Liemao; Ooi, Zi‐En; Tong, Shi Wun; Bosman, Michel; Bussolotti, Fabio; Deng, Tianqi; Wu, Gang; Yang, Shuo‐Wang; Wang, Tong; Teo, Siew Lang; et al.
Abstract: Temperature‐dependent transport measurements are performed on the same set of chemical vapor deposition (CVD)‐grown WS2 single‐ and bilayer devices before and after atomic layer deposition (ALD) of HfO2 . This isolates the influence of HfO2 deposition on low‐temperature carrier transport and shows that carrier mobility is not charge impurity limited as commonly thought, but due to another important but commonly overlooked factor: interface roughness. This finding is corroborated by circular dichroic photoluminescence spectroscopy, X‐ray photoemission spectroscopy, cross‐sectional scanning transmission electron microscopy, carrier‐transport modeling, and density functional modeling. Finally, electrostatic gate‐defined quantum confinement is demonstrated using a scalable approach of large‐area CVD‐grown bilayer WS2 and ALD‐grown HfO2 . The high dielectric constant and low leakage current enabled by HfO2 allows an estimated quantum dot size as small as 58 nm. The ability to lithographically define increasingly smaller devices is especially important for transition metal dichalcogenides due to their large effective masses, and should pave the way toward their use in quantum information processing applications. Abstract : Electrostatically defined quantum confinement in large‐area chemical vapor deposition‐grown 2D WS2 with HfO2 dielectrics grown by atomic layer deposition is reported. This marks a key milestone in scalable approaches toward 2D‐semiconductor‐based quantum devices, which has hitherto only been demonstrated with micrometer‐sized exfoliated flakes. The measurements show that low‐temperature carrier mobility is not charge impurity limited as commonly thought, but is due to another important but commonly overlooked factor: interface roughness.